Cosmetics - Rodrigues, Francisca (2021)
The cosmetic industry is a prosperous global business. According to the Cosmetics Europe—The Personal Care Association, 450 million of Europeans daily use a wide variety of cosmetic products, such as soap, shampoo, hair conditioner, toothpaste, deodorant, shaving cream, skincare, perfume, or make-up. Innovation is one of the basic principles in this field. Over the past 20 years, the innovation in cosmetic industry is enormous, resulting in a wide range of products to protect and moisturize skin as well as to combat inflammation and age signals. Also, consumers are more concerned about their appearance, trying to accept the new society paradigms. On the other hand, the demand for natural cosmetics is stronger than ever, being now widely considered a serious threat to the worldwide economy and society. These new concepts had improved the use of natural extracts as active ingredients in cosmetics, leading to the reuse of old-style active ingredients obtained from natural sources, as well as to new green compounds obtained considering sustainable principles.